Step-by-step explanation:
x+x(3)=48
combine like terms
4x=48
Divide both sides by same term
4x/4=48/4
Simplify
x=12
Answer:
2i
Step-by-step explanation:
Distribute:
(5y + 2)(y - 3)
5y^2-15y+2y-6
Which can be simplified into 5y^2-13y-6
Now the equation now looks like this: 5y^2-13y-6=-13(2+y)
For -13(2+y) multiply -13 with 2+y
Which is -26-13y
5y^2-13y-6=-26-13y
Simplify:
5y^2+20
Which can be simplified into 5(y^2+4)
y^2+4=0
y^2=-4
y=2i
Hope this helps!
The product (found when multiplying both numbers together) of 12 and 8 is 96.
The sum (found when adding both numbers together) of 12 and 8 is 20.
The difference (found when subtracting the sum from the product) of 96 and 20 is 76!